2023
DOI: 10.1155/2023/7826992
|View full text |Cite
|
Sign up to set email alerts
|

Received Signal Strength‐Based Localization for Vehicle Distance Estimation in Vehicular Ad Hoc Networks (VANETs)

Abstract: Vehicular ad hoc networks (VANETs) are an eminent area of intelligent transportation systems (ITS) which includes vehicle tracking, positioning, and emergency warnings. For protective applications, vehicle localization in the urban area is a significant problem. Global Positioning Systems (GPS) are one of the many solutions that have been offered, although they do not offer accuracy. To locate a target vehicle accurately, a unique approach called received signal strength- (RSS-) based localization scheme has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…We chose the Manhattan grid topology [17] for our VANET simulations due to its desirable properties. Figure 6 shows the grid representation of the proposed work for the VANET simulation scenario.…”
Section: Simulation Scenariomentioning
confidence: 99%
“…We chose the Manhattan grid topology [17] for our VANET simulations due to its desirable properties. Figure 6 shows the grid representation of the proposed work for the VANET simulation scenario.…”
Section: Simulation Scenariomentioning
confidence: 99%
“…Simulation results showed that, under different vehicle density scenarios, this deployment of the travel matrix could reduce the number of roadside units while enhancing vehicle communication capabilities. Ahmad et al [8] proposed a positioning scheme based on received signal strength. By detecting signals within the range of roadside devices, establishing communication, and developing an algorithm, their positioning algorithm helped determine the precise location of vehicles.…”
Section: Introductionmentioning
confidence: 99%